Григорій Сковорода і Махтумкулі Фрагі (історико-типологічне зіставлення) - Пелешенко, Ю. (Слово і Час, 2014)
У статті здійснюється історико-типологічне зіставлення творчості Григорія Сковороди і Махтумкулі Фрагі. Звернено увагу на спільність джерел світогляду обох мислителів, на роль кожного з них у розвитку української та туркменської культури. The article is an attempt at historical and typological comparison of the works by Hryhoriy Skovoroda and Magtymguly Pyragy. The main attention is paid to the common sources of the both thinkers’ worldview and to the role of each of them in the development of Ukrainian and Turkmen culture, respectively. В статье осуществляется историк о-типол огическ ое сопоставление творчества Григория Сковороды и Махтумкули Фраги. Обращено внимание на общность истоков мировоззрения обеих мыслителей, на роль каждого из них в развитии украинской и туркменской культуры.